0580 Obstructive Sleep Apnea and Daytime QT Interval by 12-Lead ECG. (12th April 2019) - Stafford, Patrick; Walker, McCall; Blackwell, Jacob; Patel, Paras; Cho, Yeilim; Mehta, Nishaki; Mazimba, Sula; Mangrum, J M; Kwon, Younghoon
Abstract: Introduction: The association between obstructive sleep apnea (OSA) and sudden cardiac death (SCD) has been described. A prolonged QT interval is a recognized marker of abnormal ventricular repolarization linked to increased risk of SCD. We hypothesized that patients with OSA would have more marked abnormalities in daytime QT interval. Methods: We identified consecutive patients who underwent clinically indicated diagnostic polysomnography with a 12-lead ECG at a single academic sleep center. Heart rate-corrected QT intervals (QTc) were compared by OSA severity class (normal/mild: apnea hypopnea index (AHI) <15/hr; moderate: 15-30; severe: >30) adjusting for age, sex, body mass index, hypertension, and heart failure (HF). Further evaluation was performed by dichotomizing patients into severe (AHI >30/hr) and non-severe (<30/hr) OSA. Logistic analysis was used to determine the association of OSA severity and abnormal QTc (>450msec / >470msec for men/women, respectively). Results: A total of 249 patients (50.2% female, mean age 57.2 [12.5]) were included. This cohort had a high burden of cardiovascular disease (73% with hypertension, 20% with HF). Abnormal QTc was present in 34% of males and 31% of females. QTc increased across OSA groups (normal/mild: 435.6 msec; moderate: 431.36; severe: 444.4, p= 0.03). Patients with severe OSA had longer QTc compared with normal/mild OSA (mean difference 10.0msec [0.5, 19.0], p=0.04). When stratified dichotomously, patients with severe OSA had longer QTc compared to non-severe (444.4 msec vs. 433.48 msec, p=0.004). Severe OSA was also associated with abnormal QTc (OR 2.68 [1.34, 5.48], p=0.006). There was significant interaction by HF status as the difference in QTc by OSA status (non-severe vs. severe) was more prominent in patients with HF (456.1 msec [435.3-476.8] vs. 480.5 [458.9-502.1], p=0.028). Conclusion: In a single sleep center cohort at elevated cardiovascular risk, patients with severe OSA had a prolonged daytime QTc compared to those with normal to mild OSA. Further, the prevalence of clinically significant abnormal QTc was higher in the severe (vs. non-severe) OSA group . The presence of severe OSA may represent a novel risk of SCD particularly in patients with HF. Support (If Any): None